Hollow man - Wick, Douglas; Marshall, Alan; Verhoeven, Paul; Columbia Pictures ([California] : Columbia Pictures, 2000)
After years of experimentation, Dr. Sebastian Caine, a brilliant but arrogant scientist working for the Defense Department, has successfully transformed mammals to an invisible state and brought them back to their original physical form. Detemined to achieve the ultimate breakthrough, Caine instructs his team to move on to phase III: human experimentation. Dr. Caine uses himself as the first subject
Title from title screen
Special features: Scene selections, trailers, interactive menus
Edited by Mark Goldblatt ; music by Jerry Goldsmith ; executive producer, Marion Rosenberg
Cast: Elisabeth Shue, Kevin Bacon, Josh Brolin, Kim Dickens, Joey Slotnick, Greg Grunberg, Mary Randle
DVD format
Dolby digital
Keywords: Assassins -- Drama